DIABETIC CARDIOMYOPATHY. RESISTIN: A CONTROL OF A MYOCARDIAL HYPERTROPHY - An. A. Aleksandrov; O. A. Shatskaya; S. S. Kuharenko; M. N. Yadrihinskaya; E. N. Abdalkina; E. N. Drozdova; M. V. Shestakova (Столичная издательская компания, 2015)
Aim. To evaluate the association of serum resistin with morphological and functional indices of hypertrophic myocardium in patients with type 2 diabetes and chronic heart failure (CHF) with preserved left ventricular ejection fraction.Material and methods. Patients (n=60; 12 men and 48 women) with type 2 diabetes and ischemic heart disease and CHF class II-III (NYHA) were included into the study. Clinical, laboratory and instrumental examinations, as well as determination of serum resistin were performed in all patients.Results. Positive correlation was found between serum resistin level and left ventricle end-diastolic pressure (LV EDP; r=0.43; p=0.02) in patients with concentric left ventricular hypertrophy (LVH). Negative correlation was found between serum resistin level and LV EDP (r=-0.61; p=0.000) in patients with eccentric LVH. A number of supraventricular extrasystoles positively correlated with the serum resistin level (r=0.34; p=0.033) in patients with concentric LVH.Conclusion. The role of "physiological" levels of resistin in the formation of cardiovascular indicators of the hypertrophic myocardium as well as possible prognostic significance of different levels of resistin for optimization of therapy are shown in patients with type 2 diabetes with CHF.